DAMPAK MEDIA SOSIAL TERHADAP KARAKTER SANGUINIS PADA ANAK USIA DINI - Salingkat, Sahrul; Bidjai, Tomi; Rahma, Rahma; sutari, Sutari; Poku, Asraty (Universitas Negeri Gorontalo, 2024)
The impact of social media is that children prefer to play cell phones or games and social media rather than interact with their friends. This study aims to determine the extent of the impact of social media on the optimistic character of early childhood conducted at ABA Luwuk Kindergarten. The method used is descriptive qualitative research method, which is a method in the form of observation, interviews. the object of this research is students while the resource persons are ABA Luwuk Kindergarten teachers, the data obtained is reduced and then concluded. From the results of the study, it was found that the impact of social media on the saunginis character